Study on the psychosocial aspects of risk-reducing salpingo-oophorectomy (RRSO) in BRCA1/2 mutation carriers in Japan: a preliminary report - Shigehiro, Mika; Kita, Mizuho; Takeuchi, Sayoko; Ashihara, Yuumi; Arai, Masami; Okamura, Hitoshi (Japanese journal of clinical oncology, 2016)
This study investigated the psychosocial aspects of risk-reducing salpingo-oophorectomy in Japan. The subjects were 16 patients who underwent risk-reducing salpingo-oophorectomy at the Cancer Institute Hospital. Worry about cancer, emotional state and cancer-specific distress level were evaluated using a four-point Likert scale, the Profile of Mood States-Short Form and the Impact of Event Scale-Revised, respectively, before and 1 year after the surgery. In addition, the subjects were interviewed regarding their expectation for the risk-reducing surgery, the effects of the surgery, and the recovery from surgery, before the surgery and at 1, 6 and 12 months after the surgery. A t-test or Wilcoxon rank-sum test was used for the analysis, and literal analects were prepared for the interview and the answers were organized per question item using NVIVO10. The results revealed that the total score for worry about breast cancer and ovarian cancer (P = 0.021) as well as the Impact of Event Scale-Revised (P = 0.021) were significantly lower 1 year after surgery, compared with the values before the surgery. Regarding the preoperative expectations for the surgery, the expectation for reducing the cancer risk was the highest. The reported effects of risk-reducing salpingo-oophorectomy on life included the appearance of menopausal symptoms, a loss of motivation and poor concentration; more effects were reported at 1 year after surgery than at 6 months after surgery. These results suggest that risk-reducing salpingo-oophorectomy can be effective for reducing worry about breast cancer and ovarian cancer and cancer-specific distress as well as contributing to a reduction in mortality from fallopian tube and ovarian related cancer.